A scale development study for identifying the levels of knowledge, perception and awareness of chemical hazard symbols - Tosun, Cemal; Tosun, Cemal (E-flow PDF Range Management Society of India editor.rmsi@yahoo.co.in, 2014)
The purpose of this study was to develop a scale to identify the levels of knowledge, perception and awareness of chemical hazard symbols of participants from a variety of backgrounds and ranging in age from 12 years to 40 and over. Experts were consulted for the contextual and the language validity of each item on the scale. In line with the opinions of the experts, the scale, consisting of a total of 25 items distributed under four sections, was applied to 462 participants of all age groups, so as to calculate the discrimination and difficulty indexes. In order to decide whether the third section of the scale is one-dimensional or two-dimensional, data obtained from the 13 multiple-choice questions constituting this section were examined using confirmatory factor analysis. Afterwards the items constituting the second and the third sections of the scale were tested in terms of their reliability. Finally, a useful scale of 24 items in four sections was prepared with tested validity and reliability. © 2014 Elsevier B.V., All rights reserved.
Keywords: Awareness; Confirmatory Factor Analysis; Hazard Symbols; Perception; Reliability; Validity